Sino-American Relations and the Dependence Theory. - Hsu, David (1994)
Keywords: dept.eco; faculty_collection; sabbatical_report

Thinker, Sailor, Brother, Spy - Maher, John (Maher & Maher, 1994)
Keywords: dept.eco; faculty_collection

What Are Lawyers Worth - Its Time to Set a Dollar Value on Our Positive Impact on the Economy - Speiser, S; Maher, J (Aba Journal, 1994)
Keywords: dept.eco; ⛔ No DOI found

The use of least median of squares in the estimation of land value equations - Thorson, James A (Journal of Real Estate Finance and Economics, 1994)
Ordinary least squares (OLS) regression is relatively sensitive to the presence of outliers in a data set. In this paper, a robust estimation method, least median of squares (LMS) is used to identify outliers in land value data. Once the outliers are identified, are the land value equations re-estimated. The results show that a few observations can have a significant effect on the estimated coefficients. Finally, the observations which were identified as outliers were examined in more detail. One cause of outliers is an omitted variable. In this case, a large fraction of the outliers were found to be observations with high development potential.
Keywords: dept.eco; least median of squares; outliers

Zoning policy changes and the urban fringe land market - Thorson, James A (Real Estate Economics, 1994)
This paper examines the effect of a zoning change on the land market in McHenry County, Illinois. One question addressed is whether zoning `'follows the market.” It is found that, for agricultural land, zoning does tend to follow the market. In addition, the effect of land prices on land use is examined. The results here, however, are mixed. In the initial years after the zoning change, a high relative price of residential land increases the probability that a parcel will be zoned residential. However, several years later, a high relative price of residential land decreases the probability that a parcel is zoned residential. This result suggests that it may take some time for a zoning change to have a significant impact on the local land market.
Keywords: dept.eco

Rates of return on art objects, the fisher hypothesis, and inflationary expectations - Matsumoto, Keishiro; Andoh, Samuel K; Hoban, James P (The Financial Review, 1994)
After surveying the evolution of the major methodologies in inflation hedging, this study presents a unique methodology that uses principal component factor analysis to separate the effects of variability in the real rate of return from the nominal rate of return. This approach allows the effects of both anticipated and unanticipated inflation on rates of return to be estimated more precisely. This study finds that art objects perform well in terms of average real rates of return and that the market, though not perfect, integrates anticipated inflation into the rates of return. However, unanticipated inflation is very often negatively related to the rates of return. Copyright © 1994, Wiley Blackwell. All rights reserved
Keywords: dept.eco; dept.fin

The professions in theory and history: the case of pharmacy - Savage, Deborah Anne (Industrial Organization, 1994)
Keywords: dept.eco; dept.fin; ⛔ No DOI found